Genomewide analysis of the Class III peroxidase gene family in apple (Malus domestica) - Yao Lu; Rongqun Ma; Kunhao Wu; Jilu Sun; Yutong Li; Jiawei Zhao; Zhenbao Qi; Guangli Sha; Hongjuan Ge; Yanjing Shi (PeerJ)
Class III peroxidases (PRXs) play a crucial role in maintaining reactive oxygen species (ROS) homeostasis, thereby influencing plant growth, development, and defense responses. To date, the roles of PRXs in apple branch development and the control of rootstock growth vigor remain poorly understood. This research aimed to exhaustively annotate and analyze the Class III PRX family in the apple genome. Ninety-nine PRX proteins were identified from the Malus domestica genome. Phylogenetic analysis revealed that the PRXs from Malus domestica and Arabidopsis thaliana were classified into six groups. McSCAN analysis indicated that tandem duplication events played a dominant role in the expansion of Malus domestica peroxidases (MdPRXs), thus purifying selection maintained their function. Most MdPRX genes contained cis-elements responsive to light and plant hormones such as abscisic acid (ABA) and methyl jasmonate (MeJA), as well as various stress factors. Although most MdPRXs possess N-terminal signal peptides, in contrast to the majority of Arabidopsis PRX gene family members that are primarily localized in the apoplast, 50 MdPRXs are localized in the chloroplasts, with only one-third predicted to be apoplastic. Analysis of their spatiotemporal expression patterns, based on transcriptome data, revealed extensive involvement in apple tissue and organ development, demonstrating distinct and specialized expression profiles. These variations are primarily attributed to differences in cis-elements within the promoter regions and their three-dimensional structural variations, rather than to their phylogenetic relationships. In rootstock-scion composite trees, the expression patterns of MdPRXs were influenced by both rootstock species and scion varieties. Unlike previous studies relying on zymogram analysis, our findings reveal that the transcriptional expression of MdPRXs is not inherently negatively correlated with the dwarfing capacity of apple rootstocks. Notably, we identified that high expression of MdPRX59 is specifically associated with vigorous rootstocks. A set of MdPRXs such as MdPRX27, MdPRX59, and MdPRX90 may affect the ROS status in stem cell niche of the axillary buds and promote the differentiation of branches. This systematic analysis provides a foundation for the further functional characterization of MdPRX genes, with the aim of improving apple rootstock dwarfing ability and branching characteristics.